END OF GEOGRAPHY OR REVENGE OF GEOGRAPHY? HUMAN SOCIETIES BETWEEN A SMOOTH, SPIKY OR FLAT WORLD - Andre Luis Sanguin (Bollettino della Società Geografica Italiana)
Submited in the course of the last years, the end of geography theory, the flat world theory and the revenge of geography theory gave rise to an intellectual debate among the North American geographers. The paper scrutinizes the constituent elements of these theories within the context of the digital revolution and the explosion of place. This debate refers to the very last boundary of geography, namely the deterritorialization in a borderless world and the rise of cyberspace. The primacy of a double-sided geography creates a dialectic of new territorialization.